A Secure Hierarchical Key Management Scheme in Wireless Sensor Network. (23rd September 2012) - Zhang, Yiying; Li, Xiangzhen; Liu, Jianming; Yang, Jucheng; Cui, Baojiang
Abstract : Due to the vulnerable environment, limited recourse and open communication channel, wireless sensor networks (WSNs) are necessary to be protected from various attacks. The key management is an important way to protect the communication in WSNs. In this paper, we present a hierarchical key management scheme (HKMS) which can efficiently enhance the security and survivability for the clustered WSNs. Different from previous works, the HKMS distributes keys based on hop counts and one-way function by the clustered architecture, which not only localizes the key things but also has no overhead. The HKMS provides the session keys among sensors and the cluster key between the cluster head and member nodes. The HKMS dynamically generates different keys based on different hops in different periods which can protect the network from the compromised nodes and reduce the high probability of the common keys without any special sensors (such as the anchor nodes). The security analysis and simulation show the HKMS can prevent several attacks effectively and reduce the energy consumption.